Study Of Electrostatic Discharge (ESD) Signals In Integrated Circuits - Choo, Wei Chien (2006)
This thesis highlights the work done to investigate selected electromagnetic (EM) wave properties related to Electrostatic Discharge (ESD). It is known that ESD events generate EM waves, and numerous authors have investigated many properties related to the waves. How ever, it was unclear whether Charged Device Model (CDM) ESD events on an Integrated Circuit (IC) generate EM waves containing certain unique properties.